Pemanfaatan Gordang Sambilan dalam Upacara Horja Godang di Mandailing Natal - Mutiara Fadhilah; Putri Azizah Nasution; Rizki Adawiyah Lubis (PT. Willy Print Art, 2024)
One of the famous local cultures in Indonesia is the Mandailing culture on the island of Sumatra. Mandailing Natal Regency is the southernmost part of North Sumatra province and directly borders West Sumatra province. This research aims to determine the use of Gordang Sambilan in Mandailing Natal and the development of Gordang Sambilan music until now. The method used is qualitative and is carried out using Focus Group Discussion (FGD) data collection techniques. The steps in Gordang Sambilan's research cannot be separated from the basic historical method, which is carried out through the stages of heuristics, criticism, interpretation and writing. The research location is in Mandailing Natal Regency, especially in Panyabungan Mandailing Natal. The results of the research determine the history of the birth of the typical Mandailing Natal musical instrument, namely the Gordang Sambilan, and its use in Mandailing Natal customs. Gordang Sambilan is one of the traditional musical ensembles that has become the identity of Mandailing. Gordang Sambilan has a special meaning and value related to community functionaries who work together to carry out customs and expand the village area and become a performance at weddings.